Ocular side effects of systemic drugs used in dermatology - Bhanu Prakash; H Mohan Kumar; Saranya Palaniswami; Borra Harish Lakshman (Wolters Kluwer Medknow Publications, 2019)
Some systemically used drugs in managing dermatologic disorders have associated severe side effects, of which eye involvement is very significant. There are various mechanisms for these drugs to cause damage to the eye. The damage to the eye can be acute as in Stevens-Johnson syndrome or chronic as with chloroquine and hydroxychloroquine toxicity. Knowledge about these drugs and information about the mechanisms and types of damage to the eye are essential. It is also important to understand the monitoring mechanisms to diagnose early and limit the damage. Newer investigative tools, especially the imaging techniques help us to diagnose the adverse effects at an early stage. All these issues are discussed in brief here.